Cross-Resistance to Imazapic and Imazapyr in a Weedy Rice (Oryza sativa) Biotype Found in Malaysia - DILIPKUMAR,M. (2018)
ABSTRACT: The Clearfield® rice production system is an effective management tool for weedy rice and other weeds in the direct-seeded rice culture. However, if farmers cultivating the Clearfield® rice disregard stewardship recommendations, the industry could face a problem of herbicide-resistant weedy rice which would occur through the selection of outcrosses. This study aimed to confirm imidazolinone-resistant weedy rice in Malaysia. The resistant weedy rice (R-WR) was found to be 67 fold more resistant to OnDuty® (premix of imazapic and imazapyr) than the susceptible weedy rice (S-WR) based on the GR50 values (rate that causes 50% inhibition of shoot growth). The Clearfield® rice cultivar was 32-fold more tolerant to OnDuty® than the S-WR. Furthermore, the R-WR was 54 and 89 fold more resistant to imazapic and imazapyr applied separately than the S-WR, respectively. The Clearfield® rice was 140- and 40-fold more tolerant to imazapic and imazapyr, respectively than the S-WR. The R-WR biotype was susceptible to non-selective herbicides glyphosate and glufosinate, as well as the selective graminicide quizalofop. Oxadiazon controlled the R-WR biotype, but pretilachlor was ineffective. The present study documented the first case of weedy rice that was cross-resistant to imazapic and imazapyr in Malaysian Clearfield® rice field.